The Effect of Diversification: By Number of Subsidiaries and Type of Relatedness on Financial Performance with Board of Directors as Moderating Variable: (Case study: Manufacturing Companies Listed in Indonesia Stock Exchange for 2016-2018) - Hutagaol, Marini Catrin; Dharmastuti, Christiana Fara (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
Diversification strategy is strategy in expanding market and products that are related or unrelated by increasing subsidiaries. This increasing is expected to increase financial performance with proper analysis. This study aims to examine the effect of diversification strategy analyzed by number of subsidiaries, type of relatedness (related-unrelated business) on financial performance and considering the moderating effect of board of directors. This research uses 197 data from 71 manufacturing companies listed on Indonesia Stock Exchange during 2016-2018. Results show that the number of subsidiaries has no effect on firm performance and the unrelated type outperform related type. This is also supported by a theory of portfolio diversification which can reduce risk. The board of directors as a moderator has no effect on the number of subsidiaries on financial performance. Meanwhile the board of directors has a positive effect on type of relatedness. This research concludes that the board of directors is able to direct what type of diversification will be taken. Keywords: Diversification strategy, Subsidiaries, Type of Relatedness (related-unrelated business), Financial Performance (ROA)